SOX17 regulates uterine epithelial–stromal cross-talk acting via a distal enhancer upstream of Ihh - Xiaoqiu Wang (Nature Portfolio, 2018)
The transcription factor SOX17 is important for uterine gland formation, fertility, and embryo implantation in mouse. Here the authors show that SOX17 is upstream of Indian hedgehog to regulate mouse uterine receptivity, and their analysis of uterine tissue from endometriosis patients suggests the same function in humans.